A knowledge marketing model: determinants of organisational resource-based capabilities on e-retail performance. (1st January 2012) - Chen, Lisa Y.
Given limited extant research on knowledge marketing, this study proposes a unified model to explain the knowledge marketing process. The present study then identifies three primary sources of distinctive capabilities that must be addressed, while empirical examination is offered to validate the hypotheses for their impact on organisational performance with regard to knowledge marketing. Empirical results support the proposed hypotheses, showing the importance of organisational resource-based capabilities in generating and underpinning knowledge marketing activities that affect e-retail performance. Results of validation analysis are further used to impede development of a value chain of the knowledge marketing model. Therefore, the model presented in this study helps businesses to clarify and understand the value of knowledge marketing in terms of its practical benefits. Implications of the research findings and the potential for future research are also discussed.